Multisystemic Resilience as a Necessary Condition for Ensuring Child Well-Being - Michałowska, Agata Aleksandra (Pedagogika Społeczna Nova, 2025)
The global community is facing multisystemic challenges, the youngest generations additionally burdened by unprecedented risks shaping their future. In the context of change and instability, resilience is a necessary element of children’s physical and mental health, their development and well-being. Building multisystemic resilience means ensuring that all systems children and youth exist in, from families and schools to countries and ecosystems, are able to cope with, adapt to, and transform, in response to current and future shocks and stresses. The article presents recent theories and research on multisystemic resilience and approaches to strengthening and building resilience. The author encourages the readers to analyze ways in which they can act within their own communities to create more resilient environments, networks and support systems that nurture the well-being of children and help them not only adapt to, but also thrive in, the world as it is today.